2017
DOI: 10.1177/0954406217706721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of textured surface on the frictional noise under line contact and sliding–rolling conditions

Abstract: Line contact and sliding–rolling movements exist widely in gears and bearings. In order to investigate the influence of surface microstructure on the frictional noise, a numerical study on the frictional noise generated by textured surfaces under line contact and sliding–rolling conditions by the use of finite element method is presented. The finite element model is established based on real surface topography. To improve the analysis reliability, friction coefficients used in the simulation are measured for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The test apparatus is the M200 friction testing machine, which can simulate the linear contact process of gear meshing (Chang et al , 2023; Li et al , 2018), and its structural schematic is shown in Figure 2(a). Tested samples were numbered before the start of the test.…”
Section: Methodsmentioning
confidence: 99%
“…The test apparatus is the M200 friction testing machine, which can simulate the linear contact process of gear meshing (Chang et al , 2023; Li et al , 2018), and its structural schematic is shown in Figure 2(a). Tested samples were numbered before the start of the test.…”
Section: Methodsmentioning
confidence: 99%
“…The experiment was conducted on a modified JPM-1 twin-disc tribo-tester. 33 The experiment was conducted at 20 C, and the specimens were lubricated with L-HL46 hydraulic oil. The L-HL46 hydraulic oil used in the test is the lubricant required by the twin-disc test-tester.…”
Section: Twin Disc Testsmentioning
confidence: 99%